Factors contributing to the development from local to international talents in SCOPE International / Ahmad Rafique Ahmad Mokhtar - Ahmad Mokhtar, Ahmad Rafique (Faculty of Business and Management, 2010)
The research entitled “Multinational factors contributing to the development from local to international talents” is conducted with three objectives which are first to identify the respondents socio demographic background and the respondents rating of importance of the area in developing international talent, second to determine differences between respondents socio demographic and the factors contributing to the development of international talent and third is to compare whether there are differences between departments to the factors contributing in developing international talent. The respondents of this study are the employees from 2 selected departments in SCOPE International which are International Trade and Foreign Market Operation. 40 questionnaires were distributed in order to complete the purpose of study. At the end of the research the researcher found that all independent variables to be important, which the factors mentioned as independent variables having positive results toward the development from local to international talents.